Comparative effectiveness of cefazolin versus cloxacillin as definitive antibiotic therapy for MSSA bacteraemia: results from a large multicentre cohort study. (21st January 2015) - Bai, Anthony D.; Showler, Adrienne; Burry, Lisa; Steinberg, Marilyn; Ricciuto, Daniel R.; Fernandes, Tania; Chiu, Anna; Raybardhan, Sumit; Science, Michelle; Fernando, Eshan; Tomlinson, George; Bell, Chaim M.; et al.
Abstract: Objectives: We compared the effectiveness of cefazolin versus cloxacillin in the treatment of MSSA bacteraemia in terms of mortality and relapse. Methods: A retrospective cohort study examined consecutive patients with Staphylococcus aureus bacteraemia from six academic and community hospitals between 2007 and 2010. Patients with MSSA bacteraemia who received cefazolin or cloxacillin as the predominant definitive antibiotic therapy were included in the study. Ninety-day mortality was compared between the two groups matched by propensity scores. Results: Of 354 patients included in the study, 105 (30%) received cefazolin and 249 (70%) received cloxacillin as the definitive antibiotic therapy. In 90 days, 96 (27%) patients died: 21/105 (20%) in the cefazolin group and 75/249 (30%) in the cloxacillin group. Within 90 days, 10 patients (3%) had a relapse of S. aureus infection: 6/105 (6%) in the cefazolin group and 4/249 (2%) in the cloxacillin group. All relapses in the cefazolin group were related to a deep-seated infection. Based on the estimated propensity score, 90 patients in the cefazolin group were matched with 90 patients in the cloxacillin group. In the propensity score-matched groups, cefazolin had an HR of 0.58 (95% CI 0.31–1.08, P = 0.0846) for 90 day mortality. Conclusions: There was no significant clinical difference between cefazolin and cloxacillin in the treatment of MSSA bacteraemia with respect to mortality. Cefazolin was associated with non-significantly more relapses compared with cloxacillin, especially in deep-seated S. aureus infections.